Higher adverse childhood experiences interference with targeted early intervention to reduce persistence of adult subacute pain: a feasibility open trial - McSwan, Joyce; Stapleton, Peta; Panwar, Catherine E. (Frontiers in Psychology, 2023)
Introduction The feasibility of an Early Subacute Pain Intervention Program was assessed for improving outcomes in patients with subacute pain and exposure to adverse childhood experiences (ACEs) at increased risk of long-term disability. Methods Eligible patients were referred by their general practitioner for an open trial of individual case management with group-based education and psychological support sessions and access to allied health services. Measures of pain, disability, and mental health were assessed at baseline, on completion of the 6-month program, and 6 months after completion. Results Thirty-nine participants (mean age 51 years, 72% women) completed the program. Pain at baseline was subacute (median duration 9.7 weeks) and of high intensity (median score 8/10), with a mean ACE score of 4.3. After completing the program, participants reported reduced pain severity and interference ( 50% reduction), risk of future disability, psychological distress, and number of unhealthy days ( 30% reduction) and were all statistically significant (p < 0.001). These gains were maintained at 6-months from the beginning of treatment. Higher ACE scores were associated with greater baseline levels of pain interference, risk of future disability, and psychological distress, and with less improvement in pain interference and psychological distress after completing the program. Discussion This program suggested pain-related disability and mental health in patients with subacute pain and ACE exposure may be improved, although with reduced efficacy with higher ACE exposure. There need to be further robust investigation to quantify the value of targeted early intervention programs in primary health care settings to help reduce subacute pain persistence and progression to chronic pain in patients at increased risk of long-term disability.